Self‐Assembly of Amphiphilic Drug–Dye Conjugates into Nanoparticles for Imaging and Chemotherapy. Issue 22 (13th October 2016) - Sun, Tingting; Lin, Wenhai; Zhang, Wei; Xie, Zhigang
Abstract: An amphiphilic drug–dye conjugate (PTX‐Pt‐BDP ) was designed and synthesized with a platinum compound as the hydrophilic head. The precursor ofPTX‐Pt‐BDP was obtained under mild conditions by means of a three‐component Passerini reaction.PTX‐Pt‐BDP could self‐assemble into nanoparticles (PTX‐Pt‐BDP NPs) in aqueous solution via a nanoprecipitation method. The obtained nanoparticles exhibited favorable structural stability in both water and physiological environment.PTX‐Pt‐BDP NPs could be endocytosed by cancer cells as revealed by confocal laser scanning microscopy and exert potent cytotoxicity. This work highlights the potential of nanomedicines from amphiphilic drug–dye conjugates for cancer cell imaging and chemotherapy. Abstract : Amphiphilic drug–dye conjugates : Supramolecular fluorescent nanomedicines (PTX‐Pt‐BDP NPs) have been prepared through the self‐assembly of amphiphilic drug–dye conjugates. PTX‐Pt‐BDP NPs possess a high drug content and could be internalized by cancer cells and exert potent cytotoxicity.